The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/ijms140611496
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Synthesis Parameters for Mesoporous Shell Formation on Magnetic Nanocores and Their Application as Nanocarriers for Docetaxel Cancer Drug

Abstract: In this work, Fe3O4@SiO2 nanoparticles were coated with mesoporous silica shell by S−N+I− pathway by using anionic surfactant (S−) and co-structure directing agent (N+). The role of co-structure directing agent (CSDA) is to assist the electrostatic interaction between negatively charged silica layers and the negatively charged surfactant molecules. Prior to the mesoporous shell formation step, magnetic cores were coated with a dense silica layer to prevent iron oxide cores from leaching into the mother system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…According to IUPAC classification, all isotherms are identified as the adsorption and desorption branch of a type IV curve, indicating the existence of mesopores. All hysteresis loops are categorized as the type H 1 loop, implying a high degree of pore‐size uniformity in the titania films . The textural parameters derived from the isotherms are comprised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to IUPAC classification, all isotherms are identified as the adsorption and desorption branch of a type IV curve, indicating the existence of mesopores. All hysteresis loops are categorized as the type H 1 loop, implying a high degree of pore‐size uniformity in the titania films . The textural parameters derived from the isotherms are comprised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…When they provided Na 2 HPO 4 -NaH 2 PO 4 as a source of OH − ions, particle size was found to increase with an increase in the initial pH of the solution. El-Toni et al observed that on increasing the concentration of ammonia beyond a certain level, the agglomeration of silica particles takes place due to the increase in the ionic strength of the reaction medium [ 113 ]. Bouchoucha et al also reported the efficiency of TEA in producing well-dispersed nanoparticles [ 114 ].…”
Section: Synthesis Of Msnsmentioning
confidence: 99%
“…The more likely properties of MSNs that tailor the biomedical performance in terms of drug or gene loading and their release are particle size, pore size, and volume. For instance, relatively smaller particle sizes were obtained using some reagents, including alcohols, amines, inorganic bases, and inorganic salts [26][27][28]. Those agents affect the kinetics of hydrolysis and condensation reactions of the silica precursor.…”
Section: Synthesis Of Mesoporous Silica Materialsmentioning
confidence: 99%